Access policies of electronic resources of selected academic libraries in Metro Manila - Edianon, Neizl S.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Aiming to provide library users' access to electronic resources for their research needs, this study examined the access policy for electronic resources of selected academic libraries in Metro Manila. The study focused on the member libraries of the Mendiola Consortium and the Aurora Boulevard Consortium. Of the 12 member libraries, only 7 head/chief librarians or library staffs knowledgeable of the member libraries access policy were successfully interviewed. Out of the 7 member libraries, only 5 of them have access policies which were then analyzed and examined.
Based on the results of the interview with the librarian respondents, in terms of providing access to academic libraries electronic resources, usernames and passwords were given to the library's affiliated users only, which can also be used for remote access. Outside/unaffiliated users do not have remote access to the member libraries' electronic resources. The outside researchers that are members of the same consortium with the member libraries they chose to visit are required to submit a referral letter from the head/chief librarian of their school to be able to access electronic and printed resources of the library. The unaffiliated library users that are non-member of the consortium should pay the library fees to access the electronic resource of the member library.
Each member library encountered challenges in providing access to electronic resources, but addressing those problems seemed to be one of the least priorities of the library. Access policies of all 5 member libraries have similarities in terms of providing access to e-resources through username and password to the affiliated users, providing remote access to both affiliated and unaffiliated users, collecting library fees to the non-members of the consortium, requiring referral letter for unaffiliated users, and for not restricting excessive downloading to affiliated users. Furthermore, access policy differences include access to printed and electronic resources to unaffiliated library users, restrictions on excessive downloading and saving files, and collecting library fees to unaffiliated users are observed to have different policy implementation for each member library's access policy.
Thesis (Bachelor of Library and Information Science)
Keywords: Electronic information resources -- Metro Manila; Academic libraries -- Metro Manila; Reference services (Libraries)